A robust cascaded strategy of in-motion alignment for inertial navigation systems - Wanke Liu; Rui Duan; Feng Zhu (International Journal of Distributed Sensor Networks)
Inertial navigation system needs to be initialized through the alignment process, before the transition into the navigation stage can be made. In this article, a robust cascaded strategy of alignment which aims to provide an automatic operating alignment strategy for different application scenarios is proposed. The robust cascaded strategy of alignment utilizes the advantages of several alignment methods to form a cascaded alignment strategy. As a result, the robust cascaded strategy of alignment can be utilized in applications with different grade inertial measurement units under complex dynamic condition. In addition, several control measures are added into the robust cascaded strategy of alignment process to increase its robustness and to ensure that acceptable performance may be attained. A filed test using two inertial measurement units (tactical-grade FSAS and micro-electro-mechanical-system-grade SBG) shows that the proposed robust cascaded strategy of alignment can achieve alignment under various dynamic conditions, such as low speed motion, turns, stationary positions, and straight motion. The mean heading error and level angle error are 0.10° and −0.08° for the FSAS, respectively, and −0.44° and −0.02° for the SBG, respectively. The root mean square of the heading error and level angle error for the FSAS are 2.08° and 0.50°, respectively, while those for the SBG are 2.95° and 1.44°, respectively.